2010
DOI: 10.1002/anie.200905000
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I)‐Catalyzed Enantioselective Synthesis of Pyrazolidines, Isoxazolidines, and Tetrahydrooxazines

Abstract: Chiral ligands (L*) and chiral anions [(S)-TriPAg] are employed in the gold(I)-catalyzed enantioselective intramolecular additions of hydrazines and hydroxylamines to allenes. These complementary methods allow access to chiral vinyl isoxazolidines, oxazines, and differentially protected pyrazolidines. PNB=para-nitrobenzoy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 276 publications
(33 citation statements)
references
References 41 publications
0
30
0
2
Order By: Relevance
“…Disappointedly, only trace amounts of product was observed under the above conditions. Taking into account the counter ion effects in gold-catalyzed reactions [3335], Ph 3 PAuOTf, produced from a combination of Ph 3 PAuCl and AgOTf in a 1:1 ratio, was investigated. To our delight, the expected product 2a could be isolated in 56% yield (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Disappointedly, only trace amounts of product was observed under the above conditions. Taking into account the counter ion effects in gold-catalyzed reactions [3335], Ph 3 PAuOTf, produced from a combination of Ph 3 PAuCl and AgOTf in a 1:1 ratio, was investigated. To our delight, the expected product 2a could be isolated in 56% yield (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…Part of the challenge of performing detailed kinetic studies of gold(I) catalyzed hydroamination reactions is that many of the most active catalysts employed are generated in situ from gold(I) trimers or the gold chloride and the corresponding silver salt, making it difficult to determine the precise concentration of catalyst employed 4. In 2009, we reported the intramolecular hydroamination reaction of allenes with hydrazine nucleophiles catalyzed by an isolable gold(I) complexes 5. We hypothesized that an intermolecular variant of this transformation could provide a valuable platform for a systematic study of the mechanism of the reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chiral piperidines could also be synthesized with good enantioselectivities; however, it was found that a related biphenyl bisphosphine complex (R)-ClMeO-BIPHEP (AuOPNB) 2 gave superior selectivities. The substrate scope was later expanded to include protected hydrazines and hydroxylamines to form chiral pyrazolidines and isoxazolidines [102].…”
Section: Asymmetric Hydroaminations Of Aminoallenesmentioning
confidence: 99%